2005
DOI: 10.1177/021849230501300405
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infections and Balloon Counterpulsation: Risk Factors and Outcome

Abstract: Between February and September 2003, 136 (5.3%) of 2,558 patients undergoing cardiac surgery were supported with intra-aortic balloon counterpulsation. There were 71 infected (group 1) and 65 noninfected (group 2) patients. Risk factors for nosocomial infections were identified by univariate and multivariate analysis. On univariate analysis, significant risk factors were operation time, balloon pump duration, ventilation hours, duration of central venous catheter placement, amount of blood transfused, left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similarly, Pawar et al found that the balloon was a risk factor for nosocomial infections in univariate analysis. 35…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pawar et al found that the balloon was a risk factor for nosocomial infections in univariate analysis. 35…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] In the studies by Beckman et al [12] and McCabe et al [13] evaluating the complications of IABP, the incidence of local wound site infection was found to be 2.2 to 5%. In a study by Pawar et al [18] including 136 patients with IABPs inserted, the most common systemic infection resulted from the respiratory system and this was attributed to the increased incidence of atelectasis and superinfection in patients who were unable to be mobilized while under the support of IABP. In another study by Goldberg et al [19] with 101 patients comparing percutaneous and surgical techniques, the rates of local (2%) and systemic (4%) infections were found to be higher in patients undergoing the surgical method.…”
Section: Discussionmentioning
confidence: 99%